OPTIMASI INTERLOCKING MAIN MOTOR VERTICAL RAW MILL TERHADAP PROSES PRODUKSI PT SINAR TAMBANG ARTHALESTARI - Abdul Rohman Rusdan Arif; Dody Wahjudi; Tri Watiningsih (Teodolita: Media Komunkasi Ilmiah di Bidang Teknik, 2020)
In  carrying  out  the  production  process  continuously,  various  things  will  arise  during  the  production process  that  can  lead  to  downtime  and  result  in  production  losses.  Vertical  Raw  Mill  is  equipment  for producing raw meal (the basic product for making clinkers) with a production capacity of 420 tons / hour. As for the Vertical Raw Mill, the milling process of raw material has been arranged to become a material with a size of 90µ and humidity <1%. In order to achieve the production target in the Vertical Raw Mill area,  an  analysis  of  the  causes  of  downtime  was  carried  out  during  January  2018  to  November  2018. Based on data from January 2018 to November 2018, the highest frequency of downtime was the presence of  high  vibration  ≥15mm/s  so  that  it  caused  Main  Motor  10.5KV  Vertical  Raw  Mill  Trip  due  to interlocking with high vibration ≥15mm/s. Based on the analysis of the high vibration interlocking process, if vibrations occur ≥15mm /s, the Main Motor switchgear coil will be switched off. To reduce the risk of downtime, an interlocking vibration program is optimized. The aim is to summarize interlocking without removing  equipment  protection  and  is  expected  to  increase  equipment  productivity  and  life  time.  After optimization  and  data  collection  during  January  2019-June  2019,  year-on-year  evaluation  results  in  a decrease in the frequency of downtime by 71.73% and reduce the loss of raw meal production by 61.15%. Keyword : Raw Meal, Vibration, Vertical Raw Mill, Downtim ABSTRAKDalam  melakukan  proses  produksi  secara  berkesinambungan,  maka  akan  timbul  berbagai  hal  selama proses  produksi  berlangsung  yang  dapat  menyebabkan  downtime  dan  mengakibatkan  kerugian  produksi. Vertical Raw Mill  merupakan peralatan untuk  memproduksi raw meal (produk dasar pembuatan clinker) dengan  kapasitas  produksi  420  ton/jam.  Adapun  di  Vertical  Raw  Mill  terjadi  proses  penggilingan  raw material  yang  sudah  diatur  komposisinya  hingga  menjadi  material  dengan  ukuran  90µ  dan  kelembaban <1%.  Guna  tercapainya  target  produksi  di  area  Vertical  Raw  Mill  maka  dilakukan  analisa  penyebab downtime selama bulan Januari 2018 sampai November 2018. Berdasarkan data selama bulan Januari 2018 sampai  November  2018,  frekwensi  downtime  terbanyak  yaitu  adanya  high  vibration  ≥15mm/s  sehingga berakibat  Main  Motor  10,5KV  Vertical  Raw  Mill  Trip  karena  interlocking  dengan  high  vibration ≥15mm/s.  Berdasarkan  analisa  proses  interlocking  high  vibration,  apabila  terjadi  vibrasi  ≥15mm/s  maka coil  switchgear  Main  Motor    akan  di  switch  off.  Untuk  mengurangi  resiko  downtime  maka  dilakukan optimasi  program  interlocking  vibration.  Tujuannya  untuk  meringkas  interlocking  tanpa  menghilangkan proteksi  peralatan  dan  diharapkan  meningkatkan  produktifitas  maupun  life  time  peralatan.  Setelah dilakukan optimasi dan dilakukan pengambilan data selama Januari 2019-Juni 2019, hasil evaluasi secara YoY  (year-on-year)  terjadi  penurunan  frekwensi  downtime  sebesar  71,73%  dan  menekan  kerugian produksi raw meal sebesar 61,15%.  Kata Kunci : Raw Meal, Vibration, Vertical Raw Mill, Downtime